Associations of herbicides with fertilizer and plant grown regulator on soybean - Dranca, Andre Cosmo; Helvig, Enelise Osco; Goes Maciel, Cleber Daniel de; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP] (Univ Estadual Centro-oeste, 2018)
The research aimed to evaluate the performance of herbicides tank mixtures with the Fertiactyl Pos (TM) foliar fertilizer and the salicylic acid plant growth regulator in the weeds control and components of soybean crop production. The experiment was conducted in the field, Guarapuava-PR, in the 2016/2017 agricultural harvest, using randomized complete block design, with fifteen treatments and five replications. The treatments were consisted by: glyphosate (G = 960 g ha(-1)); lactofen (LAC =120 g he(-1)); cloransulam-methyl (CLO = 30,2 g ha(-1)); Fertiactyl Pos (TM) (FER = 400 mL ha(-1)); acido salicilico (AS = 500 g ha(-1) of sodium salicylate); G + LAC; G + CLO; G + FER; G + AS; G + LAC + FER; G +CLO + FER; G + LAC + AS; G + CLO + AS, and controls with and without weeding. There were no reductions and/or even weed control increments for the herbicide tank mixtures with FER and AS. The treatments with LAC isolated and/or in association with AS or FER were highlighted by higher levels of visual intoxication, reduction of chlorophyll content and height of TMG 7262 RR (TM) soybean cultivar. However, the use of FER or AS in association with G + LAC resulted in grain yield higher than the weeding control, indicating attenuator potential of abiotic stress caused by herbicides.
Keywords: tank mixtures; salicylic acid; biostimulants; Glycine max L.